2011
DOI: 10.1371/journal.pbio.1001168
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evolution of the Muscles of the Pelvic Fin

Abstract: Locomotor strategies in terrestrial tetrapods have evolved from the utilisation of sinusoidal contractions of axial musculature, evident in ancestral fish species, to the reliance on powerful and complex limb muscles to provide propulsive force. Within tetrapods, a hindlimb-dominant locomotor strategy predominates, and its evolution is considered critical for the evident success of the tetrapod transition onto land. Here, we determine the developmental mechanisms of pelvic fin muscle formation in living fish s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 34 publications
1
68
0
Order By: Relevance
“…They are the sister group of all other living gnathostomes, and their embryos can be used to gain insight into the development of the last common ancestor of all vertebrates with paired appendages (45,46). During muscle development in chondrichthyans, both appendicular and body wall musculature derive from epithelial extensions of the ventral dermomyotome (47,48). DP312 labeling presented here in Scyliorhinus shows a clean boundary between labeled mesenchyme derived from the DM and unlabeled mesenchyme of presumed lateral plate origin at both fin and interfin levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They are the sister group of all other living gnathostomes, and their embryos can be used to gain insight into the development of the last common ancestor of all vertebrates with paired appendages (45,46). During muscle development in chondrichthyans, both appendicular and body wall musculature derive from epithelial extensions of the ventral dermomyotome (47,48). DP312 labeling presented here in Scyliorhinus shows a clean boundary between labeled mesenchyme derived from the DM and unlabeled mesenchyme of presumed lateral plate origin at both fin and interfin levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first method was transplantation of labelled tissues, using a modified zebrafish protocol1920 (Fig. 2).…”
mentioning
confidence: 99%
“…Somites anterior to 10 and posterior to 11 do not contribute precursors to pelvic fin muscles 17 . We also found that if the host transplant was not initially placed ventrally enough in the host during the operation then the donor precursors would fail to contribute to the pelvic fin muscles even though the a large portion of the body wall muscle would be made from the donor tissue 17 . It was clear the ventral tip of the extension was the source of the pelvic fin muscle precursors.…”
Section: Examining Pelvic Fin Muscle Formationmentioning
confidence: 97%